How Do You Play? A Comparison among Children Aged 4–10 - Delvecchio, Elisa; Li, Jian-Bin; Pazzagli, Chiara; Lis, Adriana; Mazzeschi, Claudia (Frontiers in Psychology, 2016)
Pretend play has a central role for children’s development and psychological well-being. However, there is a paucity of standardized and valid measures specifically devoted to assess the core domains involved in play activities in preschool and primary school children. The Affect in Play Scale-Preschool (4-5 years) and the Affect in Play Scale-Preschool Extended Version (6-10 years) are semi-structured parallel tools designed to explore child’s cognitive and affective processes using a standardized play task. The current study administered this 5-minutes play task to 538 Italian children aged 4-10. The purposes were to compare play abilities in boys versus girls and in preschool versus primary school children, to correlate pretend play with divergent thinking and to evaluate the structural validity of the measure along the considered age span. No differences, excepting for Organization, were found between boys and girls, whereas school age children reported higher play abilities then the younger ones. External validity was assessed using correlational analysis with the divergent thinking task (the Alternate Uses Test) for preschoolers and primary school-aged children, in line with findings from Manova. Construct validity, assessed through the Confirmatory Factor Analysis, showed good fits for the two-factor model with cognitive and affective factor for both the Affect in Play Scale-Preschool and its Extended Version. A multi-group factor analysis suggested a partial invariance of the two-factor model across preschool (4-5 years old) and primary school-aged (6-10 years old) children. Results supported the use of the Affect in Play Scale-Preschool and its Extended Version as adequate measures to assess the interplay of cognitive and affective skills in preschool and school age children. The discussion highlights clinical and research implications linked to the possibility to have a unique play task able to assess child’s affective and cognitive abilities throughout a quite wide life span (from 4 to 10 years old).